Comparative study of legal and regulatory framework of sukuk issuance in Saudi Arabia, Malaysia and the United Arab Emirates - Alharbi, Abdullah Dhaidan S (2019)
Saudi government planners have recognized, as is shown by the CMA Strategic Plan "Financial Leadership Program" (2019-2021), that the sukuk market in Saudi Arabia is relatively small when compared to emerging markets; they represent a small percentage of bank financing and GDP. The development of this market requires concerted efforts and cooperation between various parties to enhance its attractiveness to exporters and investors. The main aim of this present study is to provide suggestions for the development of the current framework of Sukuk regulation and laws in Saudi Arabia, compare it with Sukuk issuance in Malaysia and the United Arab Emirates, and examine the conclusions that follow from this comparison for the Sukuk issuance in Saudi Arabia.